Integration of a Mobile-Based Smart Measurement System to Assess the Level of Work Readiness of Vocational Students in Higher Education - Resmi Darni; Yulyanti Harisman; Dina Sukma; Efi Fitriana; Rezki Ashriyana Sulistiobudi (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study aims to develop and evaluate a mobile-based intelligent measurement system as a tool to assess work readiness and identify work readiness patterns among vocational students in facing the challenges of Industry 4.0. Through the development of this innovative system, we have successfully created a tool that can provide more accurate and efficient evaluations of students’ work readiness. The results of the study indicate that adapting to technological advancements and current labor market demands is crucial in preparing vocational graduates to succeed in an increasingly competitive workforce. It is hoped that these findings will contribute to improving the quality of vocational education and ensuring that graduates possess the relevant skills needed by the industry. In conclusion, this study not only offers practical solutions to enhance the work readiness of vocational students but also contributes to our understanding of vocational education in the Industry 4.0 era.